Kehidupan Keagamaan Anak Ulama (Studi Kasus di Kecamatan Seunagan Kabupaten Nagan Raya) - Husda, Husaini (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Ulama are people who are pious and have an important and strategic position in the historical trajectory of the people of Aceh. Every generation needs scholars as protectors and guides for the community in various aspects of life, especially in the field of religion, so it is necessary to have successors who will continue this role in each generation. And theoretically, the children of these scholars are seen as having a chance to continue this continuity. In the early decades of the 21st century in Seunagan District, Nagan Raya Regency, there were seven well-known scholars and they had 18 sons who were considered able to continue their father's roles in the past. However, in this study only 5 people (27.70%) were found to be scholars, while 13 people (62.30%) did not become scholars. This is caused by several factors; including family factors, education and environmental factors.